Field performance of asphalt pavement maintenance using Cup Lump Rubber Modified Asphalt (CMA). (May 2019) - Razali, R.; Hainin, M. R.; Hassan, N. A.; Idham, M. K.; Malek, M. S. C.; Warid, M. N. M.; Yaacob, H.; Mohamed, A.; Ismail, C. R.
Abstract: It was typical in Malaysia that pavement failures at high stressed area were due to the bituminous layer aging subjected to extreme long loading times by the slow moving of heavy commercial vehicles. This scenario causes major structural deteriorations and permanent deformation of the bituminous road surfacing. In order to fix this problem, the used of Polymer Modified Asphalt (PMA) in asphalt mixture to form PMA mixtures was selected as an alternative method to increase the durability and lifespan of the pavement. PMA had been observed for a long time in improving the performance of asphalt pavement and increase the pavement lifespan. Although, it significantly improves the quality of the asphaltic layer and prolongs the life of the pavement, the construction cost was very high. Cup lump rubber was referred to the natural rubber in frozen form and it had been used as an additive in the conventional asphalt to produce cup lump modified binder (CMB). The mixture of cup lump modified binder with aggregates will produce the cup lump modified asphalt (CMA). Recently, Public Work Department of Malaysia and Malaysian Rubber Board recently had been conducted a field study at several locations to identify the benefits and CMA levels of performance as well as the constructability of the CMA pavement in actual field site. The monitoring and testing elements in this research were including mix design, construction methods and performances monitoring. The results have been showed that the performance of CMA was not shown significant improvement as compared to conventional asphalt section after six-month construction. From the result, it was noted that the longer observation period was needed to identify the actual field performance of cup lump asphalt pavement compared to the conventional asphalt pavement.